Association between empowerment factors and the utilization of long-acting and permanent contraceptive methods among married women in Indonesia - Artini, Ni Nyoman Astri; Martha, Evi; Putra, I Gusti Ngurah Edi (Universitas Udayana, 2021)
Background and purpose: The use of long-acting and permanent methods (LAPMs) of contraception becomes one of the government’s efforts to ensure the continuity of family planning program. Factors associated with the LAPMs use can be contingent upon the study context or setting that includes socio-demographic, social and cultural norms, and women empowerment factors. This study aims to examine the associations between women empowerment and the LAPMs use. Methods: This was a cross-sectional study involving 97,316 records of married women aged 15-49 years, retrieved from three rounds of the Indonesia Demographic and Health Survey/IDHS (2007, 2012, and 2017). The dependent variable is the LAPMs use, whereas the main independent variables were women empowerment factors (i.e., educational level, occupational status, participation in household decision-making, attitude toward wife-beating). Adjusted associations between women empowerment and the LAMPs use were examined using binary logistic regression by controlling the influence of sociodemographic variables as potential confounders. Results: About half of women in this study were 35-49 years old and completed primary education. Education level was found to be positively associated with the use of LAPMs. Working women increased the likelihood of using LAPMs by 1.10 (95%CI: 1.03-1.17) times. In addition, those who approved for being beaten by their husband in any circumstance were less likely to use LAPMs (OR=0.91; 95%CI: 0.86-0.97). However, participation in household decision-making was not associated with the LAMPs use. Conclusion: Women empowerment factors that included educational level, occupational status, and the attitude toward wife-beating were associated with the use of LAPMs among Indonesian married women. Therefore, improving women empowerment by increasing women’s educational level, participation in labor force, and reducing women’s vulnerability to domestic violence can increase the uptake of LAPMs.